KORELASI DUKUNGAN KELUARGA DAN KEPATUHAN PENGOBATAN DENGAN PERILAKU KONTROL GULA DARAH PENDERITA DIABETES MELITUS - Yoyoh, Imas; Jannah, Miftahul; Fuad, Hayatun; Nopianto, Nopianto (Ensiklopedia of Journal, 2025)
Diabetes mellitus (DM) is a medical condition characterized by elevated blood sugar levels in the body, caused by impaired insulin secretion, insulin function, or both. The purpose of this study was to determine the correlation between family support and treatment adherence with blood sugar control behavior in patients with diabetes mellitus. A cross-sectional study design was used in this study. The study was conducted at Dr. Zainoel Abidin Regional General Hospital. The study was conducted in October 2024. The study population consisted of all diabetes mellitus patients at Dr. Zainoel Abidin Regional General Hospital. The study sample consisted of 75 respondents. The sampling technique used was accidental sampling. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between family support (p value: 0.04) and treatment compliance (p value: 0.00) with blood sugar levels in patients with diabetes mellitus. It is recommended that families and health workers maintain and continue to increase their support for type 2 DM patients so that they always comply with blood sugar control, such as reminding them to control their blood sugar levels, thereby preventing complications. Keywords: Diabetes, Family Support, Compliance.